Stochastic Model and Method of Optimizing the Operating Modes of a Water Network with Hidden Leaks - Тевяшев, А. Д.; Матвієнко, О. І.; Нікітенко, Г. (Харків : ТОВ «Друкарня Мадрид», 2018)
This paper is devoted to the development of a stochastic model and a method for optimizing the operating modes of a water supply network with leaks.
Keywords: water supply network; leaks; optimization; stochastic model